The bad guys - Blabey, Aaron (Blabey, Aaron. Bad guys., 2017)
The Bad Guys, Mr. Wolf, Mr. Shark, Mr. Snake, and Mr. Piranha, want to be heroes, and they decide that the way to do it is free the 200 dogs in the city dog pound--but their plan soon goes awry.